Are generalist Aphidiinae (Hym. Braconidae) mostly cryptic species complexes?. (29th November 2015) - DEROCLES, STEPHANE A. P.; PLANTEGENEST, MANUEL; RASPLUS, JEAN‐YVES; MARIE, ALEXIA; EVANS, DARREN M.; LUNT, DAVID H.; LE RALEC, ANNE
Abstract: Aphidiinae are mostly composed of specialist parasitoids and the few species described as generalist are suspected to be composed of cryptic specialists, almost indistinguishable based on morphological characteristics. The use of molecular markers has proven to be a useful tool for revealing cryptic species complexes and here we use seven mitochondrial and nuclear gene fragments to study possible genetic differentiation among seven Aphidiinae generalists. Maximum likelihood (ML) trees and Bayesian Poisson tree processes (bPTP) models were conducted on each gene separately and on the seven genes together. The standard cytochrome c oxidase I barcode region appeared to be the most polymorphic and probably the best marker to reveal putative cryptic species. However, we showed with ML trees and bPTP models that a complementary use of mitochondrial and nuclear genes was the most relevant approach to reliably identify cryptic genetic clades in the Aphidiinae. Overall, most of the analysed generalist morphospecies were shown to be composed of subgroups related to the aphid host, some of them revealed as cryptic species by the species delimitation analysis. Further studies are needed to reveal the generality of this result in Aphidiinae.